TEACHER TALK REALIZATION IN OBSERVING STAGE OF SCIENTIFIC APPROACH - Ai Setialis; Iwa Lukmana (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2018)
Observing stage is the first stage in scientific approach where students are allowed to begin the learning activities in the classroom. However, English teachers may not realize if their language use is difficult to understand by learners. To lead the successful teaching-learning activities, it is important to consider the way teachers communicate through their talk. One of the ways to analyze the teacher talk is through classroom discourse analysis. The model of classroom discourse in the present study is based on the framework of Systemic Functional Linguistics key concepts. Through the observation in four sessions and the audio-video recording, it has been found that there are 307 speech functions produced by teacher in his talk during the observing stage. Those speech functions are realized in 59 statements, 108 questions, 77 commands, and 63 acknowledgements. The data shows that teacher used those speech functions to give information and explanation to students, to get students’ attention, and to control the classroom activities by giving several directions to students. The result indicates that teacher still has the domination in the teaching-learning process, especially in observing stage. It is also shown that the teacher and students have an unequal power in the classroom.